Resistance to isoniacida, a public health problem: history and treatment - Pecho-Silva, Samuel (2019)
Despite being a preventable and curable disease, Tuberculosis continues to be a major global health problem. Worldwide, according to the WHO in 2017 were estimated at 10 million new cases of active tuberculosis, equivalent to 133 cases per 100,000 people; and about 1.3 million deaths in non-HIV patients and 300,000 additional deaths in HIV patients due to this cause, mainly in countries with limited resources. On the other hand, what exacerbates the problem is the emergence of resistance to anti-tuberculous drugs, which complicates the possibilities of treatment. Isoniazid is today one of the fundamental first-line drugs for the management of Tuberculosis, being closely related to the rapid negativization of sputum bacilloscopy, attributed to the potent bactericidal effect on rapidly multiplying strains. vital relevance not only in the control of the disease, but also in the control of the spread of the infection. The resistance to isoniazid has increased in recent years, and its presence predicts not only the greater probability of therapeutic failure, but also the potential emergence of multi-drug resistant strains. However, the molecular tests recommended today for screening and rapid detection of resistance of suspected cases do not include the evaluation of isoniazid. The relevance of the detection of isoniazid resistance for its surveillance and subsequent management is emphasized in the present review.